Pancreatoblastoma in previously pancreatic pseudocysts in a 14-year-old female: a case report (Faculty of Medicine Universitas Indonesia, 2022)
Pancreatoblastoma is a rare tumor characterized by uncontrolled growth of pancreatic epithelial cells with a mix of squamous nests and acinar differentiation. Diagnostic modalities include abnormal liver enzyme, pancreatic enzyme, and imaging findings. Treatment options include surgical resection, sometimes combined with chemotherapy, depending on the tumor’s size and grade. We reported a pancreatoblastoma in a 14-year-old female with prior pancreatic pseudocysts. The transformation from pseudocysts to pancreatoblastoma is believed to be caused by the heterozygosity molecular loss on the 11p chromosome and several genetic mutations. Magnetic resonance cholangiopancreatography showed a well-defined, heterogeneous mass in the pancreatic head, with 70% of the mass composed of cysts. A partial pancreatectomy was performed because a complete pancreatectomy may harm the adjacent structures. However, a complete resection combined with chemoradiation may be the best option for long-term survival and complete remission. In this case, she was disease-free until 30 months after the chemotherapy protocol.